2021
DOI: 10.1038/s41598-021-84047-6
|View full text |Cite
|
Sign up to set email alerts
|

Memories for third-person experiences in immersive virtual reality

Abstract: We typically experience the world from a first-person perspective (1PP) but can sometimes experience events from a third-person perspective (3PP) much as an observer might see us. Little is known about how visual perspective influences the formation of memories for events. We developed an immersive virtual reality paradigm to examine how visual perspective during encoding influences memories. Across two studies, participants explored immersive virtual environments from first-person and third-person avatar pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…We measured memory accuracy through cued recall questions that pertained to either central event details (i.e., information relevant to the main story in the scene) or peripheral event details (i.e., information in the background of the scene that was not relevant to the main story). We assessed memory accuracy for both types of event details to align with previous paradigms from the fields of autobiographical memory ( Berntsen, 2002 ), eyewitness memory ( Steblay, 1992 ; Yuille and Cutshall, 1986 ), event memory ( Iriye and St. Jacques, 2021 ), episodic memory ( Sekeres et al., 2016 ), perception ( Öhman et al., 2001 ), and virtual reality ( Gorisse et al., 2017 ). The subjective re-experiencing of memories was measured through ratings of reliving, vividness, emotional intensity, and perceived memory accuracy at both testing sessions.…”
Section: Introductionmentioning
confidence: 99%
“…We measured memory accuracy through cued recall questions that pertained to either central event details (i.e., information relevant to the main story in the scene) or peripheral event details (i.e., information in the background of the scene that was not relevant to the main story). We assessed memory accuracy for both types of event details to align with previous paradigms from the fields of autobiographical memory ( Berntsen, 2002 ), eyewitness memory ( Steblay, 1992 ; Yuille and Cutshall, 1986 ), event memory ( Iriye and St. Jacques, 2021 ), episodic memory ( Sekeres et al., 2016 ), perception ( Öhman et al., 2001 ), and virtual reality ( Gorisse et al., 2017 ). The subjective re-experiencing of memories was measured through ratings of reliving, vividness, emotional intensity, and perceived memory accuracy at both testing sessions.…”
Section: Introductionmentioning
confidence: 99%
“…A huge number of new educational opportunities can open up the use of virtual reality, as with traditional approaches, they are complex and expensive, and also require a considerable amount of time, which is not possible in the realities of modern education [1]. Among the positive qualities of using VR technologies in education, several points should be canceled:…”
Section: Resultsmentioning
confidence: 99%
“…Although we found that adopting an observer versus an own eyes perspective during retrieval impaired spatial aspects of subsequent memory, there might be some circumstances in which adopting an observer viewpoint could enhance spatial aspects of memory. For example, Iriye and St. Jacques (2021) found that memories formed from a third-person avatar perspective during immersive virtual reality were associated with greater accuracy for the spatial layout of the virtual environment, which they linked to the ability to perceive more of the surroundings when viewing the scene from a distance with respect to the location of their avatar. The mini-events used in the current study restricted the focus in memory to objects located on a tray and thus limited the potential to investigate the role of thirdperson perspectives on memory for the surroundings.…”
Section: Discussionmentioning
confidence: 99%